Association between hematobilia and primary disease after therapeutic endoscopic retrograde cholangiopancreatography - WANG Qunru (Linchuang Gandanbing Zazhi, 2017)
ObjectiveTo investigate the difference in the risk of hematobilia after therapeutic endoscopic retrograde cholangiopancreatography (ERCP) in patients with different primary diseases. MethodsA retrospective analysis was performed for the clinical data of 685 patients with pancreaticobiliary diseases who underwent therapeutic ERCP in General Hospital of Chengdu Military Region from June 2013 to June 2016. According to the presence or absence of hematobilia after ERCP, they were divided into bleeding group (29 patients) and non-bleeding group (656 patients). The association between primary disease and the risk of bleeding was evaluated. The chi-square test was used for comparison of categorical data between groups, and the independent samples t-test was used for comparison of continuous data between groups. ResultsThe overall incidence rate of hematobilia after ERCP was 4.2% (29/685), and among these patients, 21 had early bleeding and 8 had delayed bleeding. The bleeding group had a significantly higher incidence rate of hypertension than the non-bleeding group (65.5% vs 256%, χ2=22.286, P＜0.001). Compared with the non-bleeding group, the bleeding group had significantly higher proportions of patients with impacted ampullar stones (17.2% vs 4.6%, χ2=9.193, P=0.002), cholangiocarcinoma (10.3% vs 2.4%, χ2=6.437, P=0.011), pancreatic cancer (10.3% vs 3.0%, χ2=4.556, P=0.033), and ampullar carcinoma (6.9% vs 1.4%, χ2=5.356, P=0.021). There were no significant differences between the two groups in the proportions of patients with common bile duct stones, acute pyogenic cholangitis, acute biliary pancreatitis, bile duct inflammatory stenosis, and bile duct stenosis after bile duct surgery (all P＞0.05). ConclusionPatients with impacted ampullar stones or malignant pancreaticobiliary diseases have a high risk of hematobilia after ERCP and should be given adequate preoperative preparation, effective intraoperative hemostasis, and strengthened postoperative prevention.